On the best polynomial approximation of entire transcendental functions in Banach spaces. II - Vakarchuk, S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We study the behavior of the best approximations E_n(f)_E′_p of entire transcendental functions f(z) of the order ρ = 0 by polynomials of at most n th degree in the metric of the space E′_p(Ω), p ≥ 1. In particular, we describe the relationship between the best approximations E_n(f)E′_p and the logarithmic order ρ_L and type σ_L of the function f(z).